Breaking Traditional Boundaries: Problem-Solving-Based Strategies for Islamic Religious Education Curriculum Development - Mandar, Yasri; Hamimi, Tasman; Nida, Sofwatun; Rahmawati, Nur Widya; Setyaningrum, Putri Nadha (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2025)
The curriculum is a learning tool that plays a vital role in achieving educational effectiveness. In the context of Islamic Religious Education, the curriculum is designed to develop noble character, faith, and piety of students to Allah SWT. This study aims to examine the importance of developing a Problem-Based Learning-based Islamic Education curriculum to support the understanding of Islamic teachings while solving social problems solutively. This type of research method is library research with a focus on identifying innovative principles and strategies that can be applied in PAI curriculum design to make it more relevant to the challenges of modern education. The results of this study show that the problem-based learning approach in Islamic Religious Education plays an important role in developing students' critical thinking, analytical skills, and skills in distinguishing between facts and opinions. In addition, this study recommends an innovative approach that connects Islamic teachings with relevant social problem solving, thus not only improving learners' cognitive aspects, but also shaping their character, attitude, and piety in facing societal challenges with solutions based on Islamic values.